Islamic religious education in Europe: a comparative study - Franken, Leni; Gent, Bill (Routledge research in religion and education, 2021)
Islamic religious education in Europe : introduction / Bill Gent & Leni Franken -- Islamic religious education in Austria / Michael Kramer -- Islamic religious education in Belgium / Leni Franken & Caroline Sägesser -- Teaching 'religion-Islam' in Bulgarian public schools / Nonka Bogomilova -- Islamic religious education in Cypriot state schools / Dilek Latif -- Education about Islam in Danish state schools / Mette Buchardt & Nanna Ramsing Enemark -- Islamic religious education in England / Bill Gent, Mike Diboll & Farid Panjwani -- Islamic religious education in Finland / Tuula Sakaranaho & Inkeri Rissanen -- Islamic religious education in France / Diane-Sophie Girin -- Islamic religious education in German state schools / Eva-Maria Euchner & Kathrin Hackner -- Islamic religious education and teaching about Islam in Greece / Angeliki Ziaka & Marios Koukounaras Liagkis -- Islamic religious education in the Netherlands / Ina ter Avest, Cok Bakker & Leni Franken -- Education about Islam in Norwegian religious education / Bengt-Ove Andreassen -- Islamic religious education and education about Islam in Sweden / Jenny Berglund -- Islamic religious education in Switzerland / Hansjörg Schmid, Andreas Tunger-Zanetti & Monika Winter-Pfändler -- Comparative perspectives on IRE in Europe / Oddrun M.H. Bråten -- Islamic religious education in Europe and European recommendations as mutual challenges / Martin Rothgangel -- Teaching and learning about Islam in educational terms / Geir Skeie -- Varieties of Islamic religious education and the link with citizenship education / Siebren Miedema -- Democratic education on religion and ethics in Islamic religious education contexts / Olof Franck -- Teaching about Islam : insights from hermeneutics / Farid Panjwani -- Postcolonial and feminist perspectives in Islamic religious education / Marianne Bøe -- Islamic education within the Muslim minority-context of Europe : pedagogy, politics and future directions / Abdullah Sahin -- Religious education and social cohesion : a normative stance / François Levrau -- Compulsory, objective, critical and pluralistic teaching about religions? : incentives and disincentives under international human rights law / Jeroen TempermanIn -- Conclusion : post-secular 'Islamic religious education' in Europe : challenges, opportunities and prospects / Leni Franken.